Global Trends in Incidence Rates of Primary Adult Liver Cancers: A Systematic Review and Meta-Analysis - Dasgupta, Paramita; Henshaw, Chloe; Youlden, Danny R.; Clark, Paul J.; Aitken, Joanne F.; Baade, Peter D. (Frontiers in Oncology, 2020)
Background Primary liver cancer is a leading cause of cancer deaths worldwide. Global burden varies reflecting geographical distribution of viral hepatitis. Our objective was to perform a systematically review and meta-analysis of published current trends in incidence of adult liver cancers and histological types worldwide. Methods Systematic searches of PubMed, EMBASE, CINAHL and Web of Science databases for English language peer-reviewed articles published from 1/1/2008 to 01/09/2019. Inclusion criteria were population-based studies of adult liver cancer patients with quantitative estimates of temporal trends in incidence for liver cancers and/or histological types. For multiple studies from the same geographical area, only the publication that reported the most recent trends for the same cancer type and population sub-group was included. Review was conducted per PRISMA guidelines. Two authors independently extracted data and critically assessed studies. Proposed contributors to observed trends were extracted from included articles. Study-specific estimates of the annual percentage change (APC) in incidence rates with 95% confidence intervals (CI), were pooled using random effects meta-analysis models. Heterogeneity was measured using the I2 statistics and publication bias evaluated using funnel plots and Egger’s tests. Results Overall 53 studies met the inclusion criteria, of which 31 were included in the meta-analysis. Overall pooled APC estimates were +0.8 (95% CI -0.3, +2.0) for liver cancers combined, +2.6 (95% CI +1.2, +4.0) for hepatocellular carcinoma (HCC) and +4.3 (95% CI +2.5, +6.1) for intrahepatic cholangiocarcinoma . Sub-group analyses indicated increasing trends for liver cancers (APC +3.2, 95% CI +2.5, +3.9) and HCC (APC +3.6, 95% CI +2.9, +4.4) in the region of North America/Europe/Australia, whereas corresponding trends were decreasing (APC -1.7, 95% CI -2.2, -1.1) and stable (APC -0.7, 95% CI -1.9, +0.5) in Asia respectively. Conclusions Incidence is increasing for adult liver cancers and HCC in western countries, whereas trends are decreasing in Asian region, although still remaining high. Our findings highlight the importance of viral hepatitis control and lifestyle interventions to reduce global liver cancer burden. Ongoing surveillance is also vital to detect early shifts in incidence trends.